The associations between seven different types of physical activity and the incidence of fracture at seven sites in healthy postmenopausal UK women - Armstrong, MEG; Lacombe, J; Wotton, CJ; Cairns, BJ; Green, J; Floud, S; Beral, V; Reeves, GK; Million Women Study Collaborators (Wiley, 2019)
There is a paucity of information on associations between specific types of physical activity and fracture risk at different sites in otherwise healthy postmenopausal women. Therefore, we examined risk of fracture at 7 different sites associated with 7 different types of physical activity in the population-based prospective UK Million Women Study. A total of 371,279 postmenopausal women (mean age 59.8 years), rating their health as good or excellent and reporting participation in walking, cycling, gardening, doing housework, yoga, dance and sports club activities, were followed for site-specific incident fracture through record linkage to national databases on day-case and overnight hospital admissions. Cox regression yielded adjusted relative risks (RRs) and, because of the large number of statistical tests done, 99% confidence intervals (CIs) for fracture at 7 different sites in relation to 7 different physical activities. During an average follow-up of 12 years, numbers with a first site-specific fracture were: humerus (2341), forearm (1238), wrist (7358), hip (4354), femur (not neck) (617), lower leg (1184), and ankle (3629). For upper limb fractures there was significant heterogeneity across the 7 activity types (test for heterogeneity p=0.004), with gardening more than one hour/week associated with a lower risk (RR=0.91, 99%CI 0.86-0.96; p<0.0001), whereas cycling more than an hour/week was associated with an increased risk (RR=1.11, 99%CI 1.00-1.23; p=0.008). For fractures of the lower limb (including hip) there was no significant heterogeneity by type of activity, with significant approximately 5-15% reductions in risk associated with most activities, except cycling. For hip fractures, there was no significant heterogeneity by type of activity, but with significant 15-20% reductions in risk associated with walking for 1 hour/day and participating in yoga and sporting activities. Physical activity is a modifiable risk factor for fracture, but the effects differ between different types of activities and different fracture sites. This article is protected by copyright. All rights reserved.